Guitare à Versailles. Transcribing the Guitar Music of Robert de Visée for the Contemporary Instrument - Miłosz MĄCZYŃSKI (Edukacja Muzyczna)
Robert de Visée’s guitar works represent one of the pinnacles of French instrumental music during the reign of Louis XIV, the Sun King. The history of transcribing it for the six-string guitar can be traced back to the 19th century and continues uninterrupted to the present day, with a plethora of subsequent arrangements for the modern guitar. It is impossible to overstate the importance of de Visée’s music in the context of the guitar repertoire as it constitutes an invaluable source of both concert and teaching material. The transcription of de Visée’s guitar works presents a number of challenges, some of which are outlined below. The most significant distinction is the discrepancy in the tuning of Baroque and contemporary instruments, which inevitably introduces interference with the intrinsic fabric of the composition during the transcription process. The remaining issues arise naturally from the initial one and include a number of decisions that the transcription’s author is required to make. These decisions encompass a range of elements, including the transposition of notes, the manner in which voices are conducted, the type of strokes (batteries) employed, and so forth. Matters pertaining to the transcription process also include the accurate interpretation of the symbols utilized in the tablature and a comprehensive understanding of performance practices unique to French Baroque music.